UIN: STUDI ISLAM DAN ARAH BARU ISLAM INDONESIA - Hasbiyallah Hasbiyallah; Moh. Sulhan; Heri Khoiruddin; Undang Burhanudin (Islam Futura, 2019)
Islam as a religion has actually become the target of study not only by Muslims but also by non-Muslims for diverse purposes and interests with various approaches. Indonesian Islamic Studies conducted by Dutch scholars and Orientalists are mostly intended for political and policy purposes related to the fate of Muslim-majority male citizens. Islamic dynamics revealed more progressive dynamics in the 1960s and 70s when institutionally the Ministry of Religion of the Republic of Indonesia released the State Islamic Religious College (PTKIN) with the form of an Institute that developed religious scientific disciplines in the form of various faculties. From this, a variant of State Islamic University (UIN) developed with the development of study areas outside the religious. The fundamental problem that is the focus of this research relates to PTKIN's Islamic facial dynamics in the context of changes to the State Islamic University (UIN), especially Islamic studies and the new direction of Indonesian Islam which is becoming a new force at the State Islamic University (UIN). Specifically, this study aims to understand the trends and challenges of Islam in PTKIN in the future, and the Islamic thinking map of PTKIN in the new face of UIN which includes UIN SGD Bandung, UIN SUKA Yogyakarta and UIN Ar-Raniry Aceh.